2021
DOI: 10.1002/tox.23133
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying protective effects of vitamin E against mycotoxin deoxynivalenol‐induced oxidative stress and its related cytotoxicity in primary human brain endothelial cells

Abstract: Fusarium mycotoxins are one of the largest families of mycotoxins. Among these mycotoxins, deoxynivalenol is the most widespread pollutant of grains. However, the mechanism underlying the effect of deoxynivalenol on cytotoxicity in human brain endothelial cells was still unclear. This study examined whether deoxynivalenol induced oxidative stress‐associated cytotoxicity in primary human brain endothelial cells (HBEC‐5i), and explored whether Vitamin E (VE), a selective antioxidant, had protective effects on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Evidence indicates that oxidative stress serves as a significant mechanism of neurotoxicity, resulting in increased levels of reactive oxygen species (ROS) and diminished intracellular reduced glutathione (GSH) levels. , These ROS, along with reactive nitrogen species (RNS), operate as signaling mechanisms to initiate autophagy or mitophagy, both of which play a crucial role in neurotoxicity . Over the past few years, some studies have employed pig species as models to elucidate the neurotoxic effects of DON ,,, along with other in vitro models. , The potential mechanisms through which mitochondrial dysfunction contributes to diverse neurotoxic effects in the context of DON exposure remain complex, multifaceted, and unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that oxidative stress serves as a significant mechanism of neurotoxicity, resulting in increased levels of reactive oxygen species (ROS) and diminished intracellular reduced glutathione (GSH) levels. , These ROS, along with reactive nitrogen species (RNS), operate as signaling mechanisms to initiate autophagy or mitophagy, both of which play a crucial role in neurotoxicity . Over the past few years, some studies have employed pig species as models to elucidate the neurotoxic effects of DON ,,, along with other in vitro models. , The potential mechanisms through which mitochondrial dysfunction contributes to diverse neurotoxic effects in the context of DON exposure remain complex, multifaceted, and unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Pochuen et al. (2021) showed that pretreatment with vitamin E (20 μmol/L) can decrease the cytotoxicity induced by DON (10, 20, 30, 40, or 50 μmol/L) and protect cells against DON‐induced oxidative damage. Savard et al.…”
Section: Don Biological Detoxification Methods and Nutritional Mitiga...mentioning
confidence: 99%
“…They can restrain DONinduced oxidative damage by inhibiting ROS production, DNA damage, and lipid peroxidation and improving antioxidant enzyme activity. Pochuen et al (2021) showed that pretreatment with vitamin E (20 μmol/L) can decrease the cytotoxicity induced by DON (10,20,30,40, or 50 μmol/L) and protect cells against DON-induced oxidative damage. Savard et al (2016) investigated whether the combination of vitamin E (50 μmol/L) and sesamin (25 μmol/L) can prevent the production of ROS and improve the cell survival rate.…”
Section: Vitamins and Microelementsmentioning
confidence: 99%
“…Previous studies have demonstrated that the mechanism of DON-induced toxic effects is closely link with Nuclear factor E2-related factor 2 (Nrf2)/ haem oxygenase-1 (HO-1), Mitogen-activated protein kinases (MAPK) and nuclear factor-kappa B (NF-κB) signaling pathway [11][12][13]. The Nrf2/HO-1 pathway plays a vital role in mitigating intracellular oxidative stress and safeguarding cells from damage attributed to reactive oxygen species [14].…”
Section: Introductionmentioning
confidence: 99%